(untitled) (Journal of Hama University, 2024)
Introduction: The new Corona virus disease - 19 has formed a global pandemic due to its rapid spread throughout the world and resulting in a large number of deaths. Healthcare providers on the front lines have played a major role during this pandemic. To prevent transmission of infection and gain confidence in the battle against this disease, Healthcare providers were forced to wear personal protective equipment (PPE) while dealing with and providing care to patients with the emerging coronavirus - 19. Aim : This study aims to describe the challenges of using personal protective equipment among caregivers during the COVID-19 pandemic.in Syria. Design: A qualitative, descriptive, phenomenological study was conducted on a purposive sample consisting of 12 participants (10 nurses and 2 doctors), who were providing care to patients with the emerging coronavirus - 19 at Al-Haffa Hospital and Tishreen University Hospital in Latakia in the period between (10) July – (10) December, 2022. Data were collected using interviews, and the data were analyzed using Colaizzi’s (1978) method. Results: The results of the current study identified three main themes that reflected the challenges of personal protective equipment use among caregivers during the COVID-19 pandemic. These are:1- difficulties in caring for patients. 2- communication difficulties. 3- the effects of using personal protective equipment on caregivers. Conclusions: Wearing personal protective equipment for a long period negatively affects the performance of caregivers. Using a clear guideline for the use of personal protective equipment, and training caregivers to use personal protective equipment while caring for patients improves the quality of care. Recommendation: The study recommends conducting future research on the impact and effectiveness of a training program on the use of personal protective equipment on the quality of care provided during global pandemics